A utopia de Ernesto Cardenal: um poema de amor à Nicarágua Sandinista - Brandão, Letícia Araujo (2015)
This thesis aims to research the literary trajectory of Ernesto Cardenal, as well as the political consequences of his thought during the period leading up to the Sandinista Revolution, during which this revolution was developed in Nicaragua. Throughout his life, Cardenal took on not only the role of a poet, whichbrought him worldwide fame as an intellectual, but also that of a religious man and a revolutionary committed to the fight against social inequality in his country. In this way, he united ethical-Christian values to the Sandinistacause and contributed decisively to the project of construction of a hegemonic Christian and revolutionary culture that, for ten years (from the triumph of therevolutionin 1979 until the elections that brought the oppositioncandidate, Violeta Chamorro,to power in 1989), gave legitimacy to the government of the Sandinista National Liberation Front. Every trace of his human and literary thought, therefore, can be seen in his role as a formerof opinion in the period when he founded the contemplative community of Our Lady of Solentiname; and during the Revolution, in his role as Minister of Culture. Understanding the faces of Love that emanate in his life and work is, therefore, of fundamental importance for a concrete analysis of the process of formation of an alleged revolutionary cultural hegemony in Nicaragua, a fundamental project of the SNLF government which Cardenalwas part of